MORAL VALUES IN THE STORY OF NAAMAN SANG SENOPATI: A DISCOURSE ANALYSIS OF JAVANESE FOLKLORE - Widaningrum, Seruni; Pujiono, Bagong (Universitas Negeri Medan, 2023)
Wayang wahyu grows and develops among Catholics as a proclamation of church teachings. Church teachings have moral values that need to be instilled in humans for character education. Dalang presents a reflection of a life that is full of moral messages through the drama of the Wayang wahyu so that the delivery of moral messages becomes familiar to the Javanese community. This study aims to reveal the moral values contained in Lakon Naaman Sang Senopati. This research uses a qualitative descriptive method with a value analysis approach. The results of this study can be concluded that the Wayang Wahyu performance is an effort by Catholics to bring their teachings closer to the Javanese community, especially Catholics. The performance of Naaman Sang Senopati contains moral values that are useful for building the character of Catholics. The result of this study is that this performance is full of values of religiosity, trust, self-surrender, nationalism, obedience, universality, and love. The puppet revelation performance of the play Naaman Sang Senopati implies a moral message, namely: religious, trust, self-surrender, nationalist, universal, obedient, and love. These values are in accordance with the morals that must be shown as Catholics. Because by implementing these values, peace and harmony between religious communities can be realized. Naaman™s attitude of respecting other people™s principles and not imposing the beliefs of his king is a reflection of the principles of Catholics in Indonesia, namely 100% Catholics and 100% Indonesians. Being 100% Catholic is manifesting the law of love; while 100% of Indonesia is creating harmony between religious communities, solidarity, working together, helping each other, and taking part in nation-building programs. These values are expected to form a national character full of morality.